Developing a Sustainable Digital Campaign Framework: A Case of Chanaya Resort Bandung - Sekar Dinda Annisa; Vijaya Isnaniawardhani; Priyo Subekti; Evi Novianti (Lembaga Bale Literasi, 2026)
As sustainability becomes increasingly important in tourism industry. Destinations are expected to communicate sustainability values effectively through digital channels. However, existing studies on sustainability communication and digital marketing provide limited guidance on how sustainability can be systematically integrated into digital campaign planning. This study aims to develop a framework for integrating sustainability into digital campaign planning for tourism destinations. Using a Design Science Research approach, Chanaya Resort Bandung was employed as a case study. Data were collected through observations, interviews, and document analysis, followed by stakeholder validation involving academic, industry, and destination representatives. The study resulted in a Sustainable Digital Campaign Framework consisting of four interconnected layers: Strategic Foundation, Campaign Design, Campaign Execution, and Campaign Evaluation. The framework integrates audience persona and sustainability value as key inputs for developing campaign objectives, narratives, content strategies, activation activities, and evaluation mechanisms. Validation results indicate that the framework is relevant, practical, and applicable for tourism destinations. This study contributes to sustainable tourism marketing by providing a structured approach for translating sustainability values into digital communication and campaign planning.